Multiplanar MDCT Measurement of Esophageal Hiatus Surface Area: Association with Hiatal Hernia and GERD - Ouyang, Wei (Surg Endosc, 2015)
BACKGROUND: Accurate measurement of esophageal hiatus size is clinically important, especially when antireflux surgery is planned. We present a novel method for in vivo measurement of esophageal hiatal surface area using MDCT multiplanar reconstruction. We aimed to determine if large hiatal area is associated with hiatal hernia and gastroesophageal reflux disease. METHODS: We retrospectively analyzed subjects prospectively enrolled in the COPDGene(®) project. We created two test groups, one with hiatal hernia on chest CT, and one with GERD on medical treatment identified by history without hernia. Matched control groups were formed. We performed CT post-processing to define the double oblique plane of the esophageal hiatus, on which the hiatal surface area is manually traced. RESULTS: 48 subjects with hernia had larger mean hiatus areas than matched controls (6.9 cm(2) vs. 2.5 cm(2), p<0.0001), and were more likely to have GERD (42% vs. 10%, p<0.0005). Subjects with mixed (type III) hernias had larger hiatuses compared to subjects with sliding (type I) hernias, who, in turn, had larger hiatuses than subjects without hernia (p<0.0001). 55 hernia-negative subjects with GERD did not have significantly larger mean hiatal areas compared to matched controls (3.0 cm(2) vs. 2.5 cm(2), p=0.12). 20 measurements obtained by two radiologists showed correlation of 0.93, with mean difference of 0.5 cm(2) (p=0.20). CONCLUSIONS: We devised a method to measure in vivo esophageal hiatal surface area using MDCT reconstruction and established the normal size range for the first time. This methodology has the potential to guide decision-making in antireflux surgery technique pre-operatively, and assess surgical result post-operatively. Presence of hernia correlated with large hiatuses and GERD. However, hiatal area failed to identify those with GERD in the absence of hiatal hernia.